Effects of the functionalized graphene oxide on the oxygen barrier and mechanical properties of layer-by-layer assembled films. (1st May 2016) - Kim, Seon-Guk; You, Nam-Ho; Lee, Wonki; Hwang, Jun Yeon; Kim, Myung Jong; Hui, David; Ku, Bon-Cheol; Lee, Joong Hee
Abstract: An effective method to fabricate high-performance oxygen gas barrier films by alternately stacking negatively charged graphene oxide (GO) and positively charged aminno-ethyl-functionalized GO (AEGO) on PET substrates was suggested. The GO was prepared by the Hummer's method using natural graphite powder and the AEGO was synthesized by a carbodiimide reaction of the GO. High resolution transmission electron microscopy (HRTEM) and X-ray photoelectron spectroscopy (XPS) were used to characterize the introduction of functional groups of GO and AEGO. GO/AEGO/GO layers on a PET film were formed through spray coating method. The gas barrier and mechanical properties of the film were examined. One layer of GO/AEGO/GO stacked film coated on a PET substrate showed an oxygen permeability of 0.01 cc/m 2 day atm, which is 10 3 times lower than that of pure PET. The results corresponding to tensile strength and modulus of the film revealed an increase of approximately 61 and 41% compared to those of pure PET, respectively.